EFEKTIVITAS MODEL PEMBELAJARAN MULTILITERASI DALAM MENINGKATKA KEMAMPUAN MENULIS NARASI DIKELAS V SEKOLAH DASAR - Hendra Saputra; Supriyono Supriyono (Universitas Trilogi, 2017)
This research is motivated by the low writing ability of students. This study aims to improve the ability to write a narrative in grade V Durian Payung Elementary School Bandar Lampung by using a multiliterasi learning model. The research method used by the researcher is a classroom action research, with a total of 20 students. This research took place in 2 cycles, each cycle consisting of 2 actions. The techniques used in data collection are observation, tests, interviews, documentation, and field notes. The results showed that the application of a multiliterasi learning model could improve the ability to write a narrative in class V Durian Payung Elementary School in Bandar Lampung.